Impacto de los Retails Homecenter en el mercado ferretero del Distrito de Trujillo - Carruitero Villena, Elvis Eduardo (2012)
This thesis aims to identify the main impacts caused by the presence of homecenter retailers in the hardware market district of Trujillo in 2011, to this end, use a type of non-experimental research or cross-transactional because the study performed in a cut of time. In the development of research methods were applied inductive, deductive, synthetic and statistical techniques using data collection such as observation and surveys of local hardware stores and customers in the city of Trujillo, in the fourth chapter also explains in detail the city hardware market and customer profile Trujillo. We conclude that the entry of the hardware market homecenter Retails Trujillo has not led to a reduction in the growth of this market. Finally in the sixth chapter presents the proposed contingency policies for ironmongers. Under it, get this document which will form the basis and support for optimizing decision-making by investors and related item.